Implementation of QRIS: A Case Study of SMEs in Indonesia - Mohammad Mirza Munthaha; Ibnu Aqil; Syaikhu Ramadhan Maulana; Andi Sri Wahyuni; Arinal Muna (Dinasti Publisher, 2024)
After COVID-19, one of the most widely used payment methods for online purchases is the Indonesian Standard Quick Response Code (QRIS), particularly since Bank Indonesia has accepted it. Utilizing the Innovation Resistance Theory (IRT) approach, which includes two primary components—psychological and functional—this study aimed to uncover impediments to the adoption of QRIS through the use of usage, value, risk, tradition, and image barriers. SMEs in the food and beverage industry that have implemented QRIS serve as the research’s unit of analysis. Ten Majalengka-based food and beverage SMEs participated in in-depth interviews as part of this case study-based qualitative research technique. The study’s findings demonstrate that QRIS has benefits that outweight its minor drawbacks for both SMEs and consumers. Large-scale QRIS socialization, optimization, and equitable use are also under the purview of the government.